PENYELIDIKAN FORENSIK PADA KERUSAKAN BANGUNAN PASAR IKAN DI PULAU BELAKANG PADANG, KOTA BATAM, INDONESIA - Wa Ode Sumartini; Marvin Tandedi (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2023)
A deteriorated fish market building situated on Rear Padang Island in Kepulauan Riau Province, Indonesia has raised concerns among the local population. Consequently, it is imperative to assess the extent of the building's damage. To accomplish this, forensic investigations were conducted utilizing visual inspections, field measurements, and non-destructive testing using the Hammer Test. This study aims to outline and summarize the causes of the observed damage. Visual inspections revealed that more than 50% of the column web exhibited significant cracks, approximately 30% of the column's concrete had chipped off, and the steel reinforcement was extensively corroded. The Hammer Test results indicated that the column's strength was below 5 MPA. Based on these findings, it is evident that the building has sustained significant structural damage, necessitating either its demolition or comprehensive restoration and reinforcement. In its current deteriorated state, the building poses a severe risk and requires evacuation for safety reasons